Pitfalls in Root Trait Calculations: How Ignoring Diameter Heterogeneity Can Lead to Overestimation of Functional Traits - Rose, Laura (Frontiers in Plant Science, 2017)
Specific root length (SRL) and root tissue density (RTD) are ecologically functional traits which are calculated from root length or volume and root dry weight. Both can be converted into each other using the root diameter assuming roots are cylindrical. The calculation of volume from length or length from volume is however problematic because samples of roots do usually not have a constant diameter. Ignorance of the diameter heterogeneity leads to an overestimation of length and an underestimation of volume if standard formulas are used. Here I show for two datasets that SRL and RTD are overestimated on average 67 % for the two analyzed datasets, but up to 150 %, if calculated from each other. I further highlight that the volume values for the total sample as provided by the commonly used software WinRHIZOTM should only be used for objects with constant diameter. I recommend to use volume values provided for each diameter class of a sample if WinRHIZOTM is used. If manual methods, like the line-intersect method, are used roots should be separated into diameter classes before length measurements if the volume is calculated from length. Trait to trait conversions for whole samples are not recommended.